Symptoms of postpartum depression and early interruption of exclusive breastfeeding in the first two months of life Sintomas de depressão pós-parto e interrupção precoce do aleitamento materno exclusivo nos dois primeiros meses de vida - Maria Helena Hasselmann; Guilherme L. Werneck; Claudia Valéria Cardim da Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This study evaluates the association between postpartum depression and interruption of exclusive breastfeeding in the first two months of life. Cohort study of 429 infants < 20 days of age to four primary health care units in Rio de Janeiro, Brazil. Interruption of exclusive breastfeeding (outcome) was defined as the introduction of water, other types of liquids, milk, or formulas or any food. Postpartum depression was assessed using the Edinburgh Post-Natal Depression Scale. Associations between variables were expressed as prevalence ratios (baseline) and risk ratios (follow-up), with their respective 95% confidence intervals, estimated by Poisson regression with robust variance. Children of mothers with postpartum depressive symptoms were at higher risk of early interruption of exclusive breastfeeding in the first and second months of follow-up (RR = 1.46; 95%CI: 0.98-2.17 and RR = 1.21; 95%CI: 1.02-1.45, respectively). Considering mothers that were exclusively breastfeeding at the first month, postpartum depression was not associated with interruption of exclusive breastfeeding in the second month (RR = 1.44; 95%CI: 0.68-3.06). The results indicate the importance of maternal mental health for the success of exclusive breastfeeding. Avaliou-se a associação entre depressão pós-parto e interrupção precoce do aleitamento materno exclusivo nos dois primeiros meses de vida. Estudo de coorte com 429 crianças < 20 dias de idade em quatro unidades de saúde no Rio de Janeiro, Brasil. Considerou-se como interrupção precoce do aleitamento materno exclusivo a introdução de chá, água, suco, leite artificial ou qualquer outro alimento. Na avaliação da depressão pós-parto utilizou-se a Edinburgh Post-natal Depression Scale. Associações foram expressas como razões de prevalências (linha de base) e riscos relativos (primeiro e segundo meses de vida) e respectivos intervalos de 95% de confiança estimados via regressão de Poisson com variância robusta. Filhos de mulheres com sintomas de depressão pós-parto apresentam maior risco de interrupção precoce do aleitamento materno exclusivo nos dois meses de seguimento (RR = 1,46; IC95%: 0,98-2,17 e RR = 1,21; IC95%: 1,02-1,45, respectivamente). Entre mães que amamentam exclusivamente até o primeiro mês de vida, depressão pós-parto não se associou à interrupção precoce do aleitamento materno exclusivo (RR = 1,44; IC95%: 0,68-3,06). Esses achados apontam para a importância da saúde mental materna no sucesso do aleitamento materno exclusivo.